Fostering Environmental Hygiene Habits in Children with Special Needs - Hawa, Ika Ismatul; Muslam, Muslam (Atfaluna: Journal of Islamic Early Childhood Education, 2024)
Environmental hygiene is an important issue that impacts health and quality of life. As a consequence, several measures are required to keep the environment clean, including fostering environmental hygiene habits at an early age. This study aims to describe the habituation of environmental hygiene in children with special needs. The type of research used is qualitative, which is analyzed descriptively, using direct observation and semi-structured interviews with open questions involving participants, namely educators and students five to six years old. The results of this study indicate that the habituation of environmental hygiene in children with special needs at Talented Kindergarten Semarang City runs well through various methods such as hygiene songs, making costumes made from used goods, and applying the concept of Zero Waste Life Style. Personal cleanliness and toilet training are examples of habituation, which is the process of doing something repeatedly until it becomes second nature. The existence of adequate facilities can support children in maintaining cleanliness. The involvement of teachers, parents, and professionals in children's therapy influences their growth and development, in order for these activities to foster self-reliance, accountability, and environmental consciousness.